BEHAVIORAL DRIVERS OF REPURCHASE INTENTION ON SHOPEE: A STUDY OF SHOPPING EXPERIENCE, DELIVERY LENGTH OF TIME, ELECTRONIC WORD OF MOUTH, AND CUSTOMER SATISFACTION - Rahmiati, Filda; Putu Gilang Wardana Putri; Intan Syafinatun Nida (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2025)
This research seeks to identify behavioral drivers of repurchase intention on shopee marketplace. This study examines Shopping Experience, Delivery Length of Time, Electronic Word of Mouth and Customer Satisfaction to see their influence on Repurchase Intention on Shopee while also investigating the mediating role of customer satisfaction in the relationship between shopping experience and repurchase intention. This research employs quantitative methodologies using purposive sampling. This study employs primary data collecting via the distribution of questionnaires, yielding a total of 179 valid respondents. Additionally, SmartPLS v.3.3.3 is used as the data processing tool. The data indicates that the shopping experience greatly influences electronic word-of-mouth, costumer satisfaction, and repurchase intention. Customer satisfaction greatly influences repurchase intention. The shopping experience greatly influences repurchase intention mediated through costumer satisfaction. Regrettably, the delivery length of time and electronic word-of-mouth do not significantly influence repurchase intention.